Prospects for the use of paper waste in the production of biochar - Anastasia, Brikmans; Olga, Nesterova; Mariia, Bovsun; Viktoriia, Semal (Edelweiss Applied Science and Technology, 2026)
The transition of the economy to the processing of finished products is an important strategy of environmental management. Paper waste is one of the most common types of waste and is recyclable. There are studies on the possibility of recycling paper waste into biochar, but the impact of this biochar remains a poorly understood topic. This article presents the first results of the evaluation of biochar from office paper waste as a soil improver. Biochar was obtained by pyrolysis at a temperature of 800 °C for 1 hour. The analysis of the properties of biochar was carried out according to the methods of the international standard IBI. The yield of biochar compared to the weight of the original paper was about 31.5%. Biochar, characterized by a low content of carbon and nutrients. Biochar did not contain heavy metals, which means it is environmentally friendly. Biochar had a pH of 12.47, which can have a beneficial effect when applied to acidic soils. Additional tests are needed to obtain complete results, but it can be concluded that recycling office paper into biochar is an environmentally friendly way to recycle paper and create climate projects based on it.